Circulating inflammatory biomarkers can predict and characterize tuberculosis-associated immune reconstitution inflammatory syndrome - Haddow, L; Dibben, O; Moosa, M; Borrow, P; Easterbrook, P (2011)
Objective: To identify inflammatory biomarker profiles during paradoxical and unmasking tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS), and determine whether differences in biomarkers prior to antiretroviral therapy (ART) predict subsequent development of TB-IRIS. DESIGN:: Case-control study within a cohort of patients initiating ART in South Africa (n = 498). METHODS:: Participants were followed up for 24 weeks for development of TB-IRIS. Plasma samples were collected at baseline and presentation with symptoms. Groups of cases and controls were as follows: pre-ART TB and developed paradoxical TB-IRIS (n = 9); pre-ART TB but no IRIS (n = 12); no pre-ART TB but developed unmasking TB-IRIS (n = 13); no pre-ART TB and no TB or IRIS during treatment (n = 12). Concentrations of 18 cytokines and chemokines, and C-reactive protein (CRP), were measured and compared. Results: Event samples were drawn a median of 28 days after ART initiation [interquartile range (IQR) 14-56 days]. During paradoxical TB-IRIS events, there were lower median concentrations of interleukin-10 [IL-10; 22.1 (IQR 15.3-34.9) vs. 82.2 (29.4-128.4) pg/ml, P = 0.047] and monocyte chemotactic protein-1 [MCP-1; 27.6 (20.0-29.7) vs. 71.4 (40.6-77.8) pg/ml, P = 0.005], and higher CRP: IL-10 ratio [2.2 × 10 (1.8-3.4) vs. 0.3 × 10 (0.2-0.5), P = 0.003] than in controls. Patients who developed unmasking TB-IRIS had higher median pre-ART levels of CRP [25 (8-47) vs. 6 (lower limit of detection, LLD-12) mg/l, P = 0.046] and interferon gamma (IFN-γ) [9.1 (4.4-24.7) vs. 0.9 (LLD-8.7) pg/ml, P = 0.032] than controls. Conclusion: Patients with unmasking TB-IRIS had higher pre-ART levels of plasma IFN-γ and CRP, consistent with preexisting subclinical TB. Paradoxical TB-IRIS was associated with lower levels of biomarkers of monocyte and regulatory T-cell activity, and higher CRP. © 2011 Wolters Kluwer Health - Lippincott Williams and Wilkins.